3-Acetyloxy-2-cyano-2-(alkylaminocarbamoyl)propyl Groups as Biodegradable Protecting Groups of Nucleoside 5 '-mono-Phosphates - Ora M; Mantyvaara A; Lonnberg H (MDPI AG, 2022)
Thymidine 5`-bis[3-acetyloxy-2-cyano-2-(2-phenylethylcarbamoyl)propyl] phosphate (1) has been prepared and the removal of phosphate protecting groups by hog liver carboxyesterase (HLE) at pH 7.5 and 37 degrees C has been followed by HPLC. The first detectable intermediates are the (R(P))- and (S(P))-diastereomers of the monodeacetylated triester 14, which subsequently undergo concurrent retro-aldol condensation to diester 4 and enzyme-catalyzed hydrolysis to the fully deacetylated triester 15. The former pathway predominates, representing 90% of the overall breakdown of 14. The diester 4 undergoes the enzymatic deacetylation 700 times less readily than the triester, but gives finally thymidine 5`-monophosphate as the desired main product. To elucidate the potential toxicity of the electrophilic 2-cyano-N-(2-phenylethyl) acrylamideby-product 17 released upon the deprotection, the hydrolysis of 1 has also been studied in the presence of glutathione (GSH).